2017
DOI: 10.1002/ejp.1156
|View full text |Cite
|
Sign up to set email alerts
|

Somatotopic effects of rTMS in neuropathic pain? A comparison between stimulation over hand and face motor areas

Abstract: Strict somatotopic targeting of rTMS does not appear warranted for the treatment of upper limb or face NP. Since the hand motor area is easier to target and provides better results, it might be privileged for both types of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 48 publications
1
41
0
3
Order By: Relevance
“…From those, 29 were selected for full-length text retrieval and 14 met the selection criteria. 28 41 Hand search of the references from the eligible studies revealed two more studies that were also included in the full-length text retrieval phase but that did not meet the inclusion criteria. Figure 1 depicts a more detailed description of this process using a PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From those, 29 were selected for full-length text retrieval and 14 met the selection criteria. 28 41 Hand search of the references from the eligible studies revealed two more studies that were also included in the full-length text retrieval phase but that did not meet the inclusion criteria. Figure 1 depicts a more detailed description of this process using a PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, ten references were not included as individualized OFP data could not be extracted from the accessible results, which included chronic pain disorders that can be present in the face. Thus, 11 TMS 28 38 and 3 tDCS 39 41 studies were included in this systematic review providing data on a total of 228 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Our literature search located 19 studies that examined the clinical usefulness of rTMS to control chronic NP (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(27)(28)(29)(30)(31)(32)(33). Among the 19 studies, two were randomized controlled trials (RCTs) (19,23).…”
Section: Neuropathic Pain Of Various Originsmentioning
confidence: 99%
“…In 2016, three more studies (27)(28)(29) supported that rTMS stimulation over the M1 effectively relieved NP. Furthermore, studies conducted in 2017 and 2018 reported that high-frequency (5-20 Hz) stimulations effectively controlled NP (30,31,33). In contrast to these positive results, two prospective observational studies (13,15) and one case study (32) reported that there were no differences between rTMS and sham stimulations on NP relief.…”
Section: Neuropathic Pain Of Various Originsmentioning
confidence: 99%
“…Die Spule sollte entweder über dem motorischen Hotspot der Hand oder einer Muskelgruppe in der Schmerzregion oder mit einem MRT-/fMRT-basierten Navigationssystem über M1 der Hand oder der motorkortikalen Repräsentation der Schmerzregion positioniert werden. Eine Studie [47] zeigte, dass bei Gesichtsschmerzen rTMS über dem Hotspot der Hand wirksamer ist als über dem Hotspot des Gesichtes. Demnach könnte der Hotspot für die Hand die beste Spulenposition sein, ungeachtet der Lokalisation des Schmerzes.…”
Section: Andere Kortikale Stimulationsorteunclassified